The Application of Reader-Response Theory in EFL Teaching and Learning in Nigeria - Abraham Temitayo Adewoye (FOSTER: Journal of English Language Teaching, 2022)
This research article focuses on the interventions to enhance English language teaching and learning through literature in Nigeria's senior secondary school educational system. The research looks at the application of reader-response theory to the teaching of literature to realize its ability to improve students' quantity and consistency of talk in the English language classroom. The underlying ideas were that the reader-response approach, which used techniques like literature circles, would broaden the reach of communicative language instruction beyond literature-based classrooms and provide the ability to build learner independence outside of the classroom. However, the study would also emphasize the advantages of this technique, such as increasing language competence and abilities and offering more suitable cognitive difficulties to Nigerian senior secondary school students enrolled in an English language course. The results suggest that the basis of knowledgebase, in this case, the high school curriculum, did not lay a strong knowledge base framework.